2019
DOI: 10.2174/1871530319666190211163245
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Infection in Febrile Patients with Hematologic Malignancies Undergoing Chemotherapy in Iran

Abstract: Background: Patients with hematological malignancies undergoing cytotoxic chemotherapy are susceptible to develop invasive fungal infections particularly Aspergillus and Candida spp. Early detection of these infections is required to start immediate antifungal therapy and increase the survival of these patients. Method: Our study included consecutive patients of any age with hematologic malignancies who were hospitalized to receive chemotherapy and suffer from persistent fever (rectal temperature >38.5°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In the study of Fracchiolla et al, the mean age of patients was higher, and there was no significant relationship with the type of fungus 18 . AML was the most common malignancy, consistent with findings by Sheikh Baha'i et al and Mishra et al 13 who showed that AML was the most frequent risk factor for IFIs 24 . Another study in Japan also reported AML as the most common type of malignancy complicated by IFIs 12 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the study of Fracchiolla et al, the mean age of patients was higher, and there was no significant relationship with the type of fungus 18 . AML was the most common malignancy, consistent with findings by Sheikh Baha'i et al and Mishra et al 13 who showed that AML was the most frequent risk factor for IFIs 24 . Another study in Japan also reported AML as the most common type of malignancy complicated by IFIs 12 .…”
Section: Discussionsupporting
confidence: 89%
“…Candidemia and IA are associated with poor prognosis and a mortality rate of 33% and 42%, respectively. Mucormycosis has the worst prognosis among IFIs, with a mortality rate of 64% 11 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This condition commonly results from chemotherapy, and many studies have confirmed its critical role as a risk factor for IFI. Additionally, various other risk factors for IFI have been identified (18)(19)(20). A study involving 102 patients with hematological malignancies in Iran found that being over 60 years old, having diabetes mellitus, a previous history of IFI, receiving more than three types of antibiotics, and undergoing more than eight chemotherapy courses were significant risk factors for IFI (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, various other risk factors for IFI have been identified (18)(19)(20). A study involving 102 patients with hematological malignancies in Iran found that being over 60 years old, having diabetes mellitus, a previous history of IFI, receiving more than three types of antibiotics, and undergoing more than eight chemotherapy courses were significant risk factors for IFI (19). Another study from Spain identified corticosteroid treatment and recent viral infection as risk factors in patients with hematological malignancies, with only 12% of these patients being neutropenic (20).…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] In a recent study conducted by Sheikhbahaei et al ., it was shown that fungal culture established only 17% of samples as positive, while all of the surveyed samples (with clinical presentation related to IFIs) showed positive results when analyzed using reverse transcription-PCR. [ 56 ]…”
Section: Diagnosismentioning
confidence: 99%